Loser-effect duration evolves independently of fighting ability. Issue 1903 (29th May 2019) - Okada, Kensuke; Okada, Yasukazu; Dall, Sasha R. X.; Hosken, David J.
Abstract : Winning or losing contests can impact subsequent competitive behaviour and the duration of these effects can be prolonged. While it is clear effects depend on social and developmental environments, the extent to which they are heritable, and hence evolvable, is less clear and remains untested. Furthermore, theory predicts that winner and loser effects should evolve independently of actual fighting ability, but again tests of this prediction are limited. Here we used artificial selection on replicated beetle populations to show that the duration of loser effects can evolve, with a realized heritability of about 17%. We also find that naive fighting ability does not co-evolve with reductions in the duration of the loser effect. We discuss the implications of these findings and how they corroborate theoretical predictions.